2004
DOI: 10.1152/ajpheart.00629.2003
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial insulin resistance associated with chronic hypertriglyceridemia and increased FFA levels in Type 2 diabetic patients

Abstract: dial insulin resistance associated with chronic hypertriglyceridemia and increased FFA levels in Type 2 diabetic patients. Am J Physiol Heart Circ Physiol 287: H1225-H1231, 2004. First published May 6, 2004; 10.1152/ajpheart.00629.2003.-We evaluated the influence of chronic hypertriglyceridemia and endothelial dysfunction on myocardial glucose uptake (MGU) in Type 2 diabetic patients without coronary heart disease. Patients were divided into two groups according to fasting triglyceride (TG) levels: 5.4 Ϯ 1.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…In line with these suggestions, our group (19), by means of positron emission tomography, showed that high FFA levels are to be considered an additional risk for myocardial insulin resistance associated with endothelial dysfunction, in type 2 diabetic patients without cardiovascular disease.…”
mentioning
confidence: 64%
“…In line with these suggestions, our group (19), by means of positron emission tomography, showed that high FFA levels are to be considered an additional risk for myocardial insulin resistance associated with endothelial dysfunction, in type 2 diabetic patients without cardiovascular disease.…”
mentioning
confidence: 64%
“…Thus cardiac insulin resistance is a feature of db/db mice, at least with respect to deoxyglucose uptake. It must be acknowledged, however, that the degree of cardiac insulin resistance in db/db mice in vivo could be more pronounced because of the presence of circulating factors such as elevated plasma FA concentrations and adipokines (25,28,30). Therefore, an important objective for future investigations will be to investigate insulin sensitivity of the heart and other insulin target organs with in vivo methodologies applied to db/db mice.…”
Section: Discussionmentioning
confidence: 99%
“…Longterm estrogen replacement treatment might protect the cardiovascular system by decreasing blood pressure and inducing the expression of IRS-1 in myocardium. 22 Based upon (i) our recently published observation that E2 treatment decreases the FFA plasma level, 23 which is important for cardiac insulin sensitivity and heart fuel utilization, 24,25 (ii) data indicating that insulin and E2 regulate the same processes in the heart, 20 (iii) reports that E2 exerts non-genomic effects through the PI3K/Akt pathway, 26,27 and (iv) data indicating that E2 regulates genes of some insulin signaling molecules, [28][29][30] we initiated the present study on the hypothesis that E2 unquestionably influences heart insulin signaling.…”
Section: Introductionmentioning
confidence: 99%